Directive Control Behaviors dalam Kepemimpinan Pendidikan: A Systematic Literatur Review - Riva Yullanda; Hadiyanto Hadiyanto; Sulastri Sulastri (Yayasan Adra Karima Hubbi, 2026)
(This study aims to examine more systematically aboutdirective control behaviors in educational leadership using an approachsystematic literature review (SLR). This approach is used to identify, select, and synthesize various relevant previous research findings to obtain a more comprehensive understanding of the forms, contexts, and impacts of directive and controlling leadership behaviors in educational settings. This study used a selection process through the PRISMA stages (identification, screening, eligibility, and inclusion) to obtain 30 journal articles that met all criteria for further analysis. The articles analyzed were limited to publications from 2020-2026 with inclusion criteria including reputable scientific journals, full-text availability, and discussions of directive leadership in the educational context. The results of the study indicate thatdirective control behaviors In educational leadership, it generally appears in the form of direct instruction, strict supervision, and centralized decision-making by the leader. These behaviors have a variety of impacts, both positive in terms of improving discipline and clarity in tasks, but also negative in terms ofdirective control behaviors It can also reduce the independence and creativity of teachers and school administrative staff. These findings indicate that the effectiveness of directive leadership is highly dependent on the organizational context and the level of human resource preparedness in the school.